A case of a middle-aged patient with a ventricular septal defect complicated by severe pulmonary hypertension-stepwise surgical repair with pulmonary vasodilators-. Issue 3 (September 2021) - Kanai, Anna; Koitabashi, Norimichi; Akagi, Satoshi; Sorimachi, Hidemi; Ishibashi, Yohei; Nagasaka, Takashi; Takama, Noriaki; Soma, Katsura; Yao, Atsushi; Kasahara, Shingo; Kurabayashi, Masahiko
Abstract : We report a case of ventricular septal defect (VSD) in which we attempted to treat pulmonary arterial hypertension (PAH) with the goal of VSD closure in an adult with suspected Eisenmenger syndrome in childhood. Four years previously (age 41 years), she was referred to our department due to repeated hemoptysis requiring further treatment of PAH. We started combination therapy with several pulmonary vasodilators. Two years later, her pulmonary vascular resistance (PVR) was improved but still not at the level where VSD closure was possible. To control the increased PA flow resulting from intensive PAH treatment and to reduce the risk of hemoptysis, we performed pulmonary artery banding (PAB). As the risk of hemoptysis decreased, a prostacyclin analog was introduced, and the dose was increased. More than 1 year after PAB, active vasoactivity testing became positive, suggesting that the pulmonary vascular lesion was now "reversible". We performed VSD closure and atrial septal defect creation even though her PVR was still high. After the operation, her exercise capacity was remarkably improved. We suggest that stepwise surgical repair with pulmonary vasodilators is an important treatment option for select patients with VSD with severe PAH. <Learning objective: Advances in pulmonary arterial hypertension (PAH) treatment have led to the use of a "treat-and-repair" strategy to close the intracardiac shunt after PAH treatment in select patients with adult congenital heart disease. In our case, ventricular septal defect (VSD) closure was achieved with stepwise surgical repair and a combination of pulmonary vasodilators, even though long-standing severe PAH with persistent hemoptysis remained. Even after a long period of exposure to high blood flow, this strategy may reduce pulmonary vascular resistance and permit eventual closure of the VSD.>